Leukemia risk assessment of exposure to low-levels of benzene based on the linearized multistage model - Jin, Kexin; Zhu, Fukang; Wu, Bo; Li, Minyan; Wang, Xue; Cheng, Xiurong; Li, Ming; Huang, Deyin; Xing, Caihong (Frontiers in Public Health, 2024)
Objectives To assess leukemia risk in occupational populations exposed to low levels of benzene. Methods Leukemia incidence data from the Chinese Benzene Cohort Study were fitted using the Linearized multistage (LMS) model. Individual benzene exposure levels, urinary S-phenylmercapturic acid (S-PMA) and trans, trans-muconic acid (t, t-MA) were measured among 98 benzene-exposed workers from factories in China. Subjects were categorized into four groups by rounding the quartiles of cumulative benzene concentrations (< 3, 3–5, 5–12, ≥12 mg/m3·year, respectively). The risk of benzene-induced leukemia was assessed using the LMS model, and the results were validated using the EPA model and the Singapore semi-quantitative risk assessment model. Results The leukemia risks showed a positive correlation with increasing cumulative concentration in the four exposure groups (excess leukemia risks were 4.34, 4.37, 4.44 and 5.52 × 10−4, respectively; Ptrend < 0.0001) indicated by the LMS model. We also found that the estimated leukemia risk using urinary t, t-MA in the LMS model was more similar to those estimated by airborne benzene compared to S-PMA. The leukemia risk estimated by the LMS model was consistent with both the Singapore semi-quantitative risk assessment model at all concentrations and the EPA model at high concentrations (5–12, ≥12 mg/m3·year), while exceeding the EPA model at low concentrations (< 3 and 3–5 mg/m3·year). However, in all four benzene-exposed groups, the leukemia risks estimated by these three models exceeded the lowest acceptable limit for carcinogenic risk set by the EPA at 1 × 10−6. Conclusion This study demonstrates the utility of the LMS model derived from the Chinese benzene cohort in assessing leukemia risk associated with low-level benzene exposure, and suggests that leukemia risk may occur at cumulative concentrations below 3 mg/m3·year.